Agronomic and biochemical expression of Zinc, Manganese, and Phosphorus interaction in sweet corn plants (Zea mays L Var. Saccharata (sturtev.) L. H. Bailey) - Soltangheisi, Amin (2015)
Zinc and phosphorus have antagonistic effects on the absorption and translocation of each other in plants. Phosphorus-induced Zn deficiency is more common than Zn-induced P deficiency because growers commonly apply large amounts of P fertilizer as compared to Zn fertilizer. Manganese and Zn also interact with each other and this interaction can affect the yield of corn plants. This research was conducted to examine the effects of different levels of Zn, Mn, and P on the yield, Zn, Mn, and P concentrations and uptake, the ultrastructure of chloroplast, physiological characteristics, root growth parameters, and chlorophyll contents of sweet corn plants. Sweet corn was grown in nutrient culture containing all combinations of Zn as ZnSO4.7H2O at levels of 0.0, 5.0, 10.0, and 20.0 mg L-1 and of P as KH2PO4 at levels of 0.0, 20.0, 40.0, and 80.0 mg L-1. The treatment Zn0P20 produced the highest yield and the yields decreased with P application in combination with Zn. The lowest dry weight of young corn plants was recorded under Zn0P80 treatment at both harvesting times due to both Zn deficiency and P toxicity. Chlorophyll content decreased with high Zn and P applications and this can be attributed to the interactions of Zn and P with iron in the growth medium. The study has shown that Zn deficiency can enhance P uptake and translocation to such an extent that P may accumulate to toxic level in leaves. Sweet corn was grown in nutrient culture containing all combinations of P at levels of 0.0 and 80.0 mg L-1 as KH2PO4 and Zn at levels of 0.0 and 20.0 mg L-1 as ZnSO4.7H2O, and harvested at 14 and 28 days after transplanting. Phosphorus and Zn concentrations in leaves increased with increasing P and Zn concentration in nutrient solution. Zinc supply did not affect P concentration but Zn concentration reduced with increasing P supply in nutrient solution at both harvests. Carbonic anhydrase activity in leaves was enhanced with increasing Zn levels and decreased with increasing P levels at both harvest times. Carbonic anhydrase activity is a better indicator of Zn nutritional status than Zn concentration alone. The ultrastructure of chloroplast was affected by P and Zn supply. Sweet corn was grown in nutrient culture containing all combinations of Zn and Mn at levels of 0.0, 0.1, 1.0, and 10.0 mg L-1 as ZnSO4.7H2O and MnSO4.H2O, respectively and harvested at 28 days after transplanting. Manganese and Zn concentrations in roots and shoots increased with increasing Mn and Zn concentration in nutrient solution. Zinc concentration in both roots and shoots was enhanced with increasing Mn levels. Manganese concentration in shoots did not show any correlation with Zn concentration in nutrient solution but Mn concentration in roots decreased with increasing levels of Zn. The lowest dry weight of young corn plants was recorded under Zn10Mn0 treatment due to Mn deficiency. Sweet corn grown in pot culture containing all combinations of Zn at levels of 0.0, 5.0, and 10.0 mg kg-1 soil and P at levels of 0.0, 50.0, 100.0, and 200.0 mg kg-1 soil as ZnSO4.7H2O and KH2PO4, respectively and harvested at 28 days after transplanting showed dry matter yield increased with P supply, while Zn application did not show any significant effect on this parameter. Zinc and P uptake by shoots increased with increasing Zn and P application to the soil. Zn concentration in shoots decreased with increasing P supply, but P concentration and uptake was enhanced. Phosphorus-induced Zn deficiency in this study is mostly related to the dilution effect. The percentage of P derived from fertilizer reduced with increasing Zn application, although P uptake by shoots was unchanged.